Effect of the treatment‐before‐deposit policy on trust in physicians and perceived service quality among patients in 12 hospitals in China. (3rd August 2018) - Lee, Shinduk; Wang, Wenxin; Washburn, David J.; Shi, Hongmei; Yu, Yue; Du, Yuxian; Zhang, Hao; Maddock, Jay E.
Summary: This study examined effects of the treatment‐before‐deposit policy on Chinese patients' trust in physicians and perceived service quality. This study included 3313 patients recruited from 12 hospitals in China. The research team used cross‐sectional survey to examine Chinese patients' experience with the treatment‐before‐deposit policy, perceived service quality, and trust in their physicians. Using mediation analysis, we estimated direct and indirect effects of the treatment‐before‐deposit policy on patients' perceived service quality and trust in their physicians. Patients who benefitted from the treatment‐before‐deposit policy reported greater service quality and higher trust in their physicians. The impacts of whether patients benefitted from the policy on trust in physicians were fully mediated by perceived service quality with statistically significant indirect effect. The results support the hypothesis that the treatment‐before‐deposit policy improves patients' perceived service quality and trust in physicians.